Haplotypes of the plasminogen activator gene associated with ischemic stroke - Saito, Kosuke; Nakayama, Tomohiro; Sato, Naoyuki; Morita, Akihiko; Takahashi, Teruyuki; Soma, Masayoshi; Usami, Ron (Thrombosis and Haemostasis, 2006)
Ischemic stroke (IS) is thought to be a multifactorial disorder associated with genetic backgrounds and environmental factors. In the circulating plasma, tissue plasminogen activator (tPA) catalyzes the reaction from plasminogen to plasmin. If there is a functional disability of tPA, induction of thrombosis and infarction disorders can occur. The aim of this study was to performa haplotype-based case-control study using single nucleotide polymorphisms (SNPs) in the human tPA gene, and to assess the association between the tPA gene and IS. We genotyped 182 IS individuals and 403 controls for five SNPs in the human tPA gene, rs7007329, rs732612, rs8178750, rs2020922, and rs4471024. Using these five SNPs, a haplotype-based case control study was performed. There were seven SNP combinations that exhibited significant differences in the overall distribution between the IS and control groups. Linkage disequilibrium analysis showed that the combination of rs7007329 and rs8178750 was useful in identification of the susceptibility haplotype. The frequency of the G-T haplotype at rs7007329-rs8178750 was significantly higher in the IS group (1.2%) as compared to the control group (0.0%) (p=0.003).Diplotype analysis also showeda significant association of the diplotype with the G-T haplotype at rs7007329-rs8178750 (OR:11.4, 95%CI:1.32–97.9, p=0.013). These results suggest that the G-T haplotype at rs7007329-rs8178750 of the tPA gene isa genetic marker for IS, and that tPA ora neighboring gene isa susceptibility gene for IS.
Keywords: Tissue plasminogen activator; ischemic stroke; haplotypes; association studies; genetics